Effects of empathy, moral obligation, self-efficacy, social support and experiential learning on social entrepreneurship competencies at universities in Guangdong, China - Yunfeng, Wen (2025)
Social entrepreneurship is increasingly acknowledged as an effective approach to addressing complex societal challenges. However, research on social entrepreneurship education remains limited, especially within the context of Chinese higher education, where the impact of experiential learning has not been fully explored.This study examines how social entrepreneurial antecedents, including empathy, moral obligation, self-efficacy, and social support, influence the development of social entrepreneurship competencies. It also explores the moderating role of experiential learning, using the Theory of Planned Behavior (TPB) and Experiential Learning Theory (ELT) as the theoretical framework.A cross -sectional design employing stratified random sampling was used. Data were collected through self-administered questionnaires from 520 students enrolled at 25 Enactus-affiliated universities in Guangdong Province, China.The results indicate that self-efficacy, moral obligation, and social support significantly enhance social entrepreneurship competencies, whereas empathy does not exhibit a direct effect.Experiential learning demonstrates a strong positive impact on competencies and significantly moderates the relationships between empathy, moral obligation, and social entrepreneurship competencies.These findings highlight the critical role of experiential learning in enhancing the effectiveness of social entrepreneurship education. The study contributes to the refinement of the integrated TPB-ELT framework and provides practical implications for educators, policymakers, and institutional leaders aiming to strengthen the social entrepreneurship ecosystem within Chinese higher education